1997
DOI: 10.1093/oxfordjournals.eurheartj.a015465
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between resting heart rate and all-cause, cardiovascular and cancer mortality

Abstract: The resting heart rate is a predictor of mortality, independent of major cardiovascular risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
109
2
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(124 citation statements)
references
References 25 publications
10
109
2
3
Order By: Relevance
“…These data corroborate previous evidence on the significance of HR variability for clinical manifestations of coronary artery disease. [1][2][3][4][5][6][7] The association between low HR variability and the progression of coronary artery disease was not explained by common risk factors for atherosclerosis, or by the severity of ischemic heart disease at the time of analysis of HR variability, supporting the view that there may be an independent relationship between HR variability and the progression of coronary atherosclerosis. Despite the epidemiological evidence of an association between low HR variability and cardiovascular mortality, [5][6][7] the causes and mechanisms of this association have not been well known.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…These data corroborate previous evidence on the significance of HR variability for clinical manifestations of coronary artery disease. [1][2][3][4][5][6][7] The association between low HR variability and the progression of coronary artery disease was not explained by common risk factors for atherosclerosis, or by the severity of ischemic heart disease at the time of analysis of HR variability, supporting the view that there may be an independent relationship between HR variability and the progression of coronary atherosclerosis. Despite the epidemiological evidence of an association between low HR variability and cardiovascular mortality, [5][6][7] the causes and mechanisms of this association have not been well known.…”
Section: Discussionmentioning
confidence: 72%
“…[1][2][3] Ambulatory ECG recordings have shown that the minimum HR measured during a 24-hour period is even more closely related to cardiac events than the casual HR or 24-hour average HR, 26 and blunted circadian rhythm of autonomic modulation of HR has been described in patients with coronary artery disease. 22 In this study, the elevated minimum HR during sleeping hours, but not the maximum HR, was found to be related to the progression of coronary artery stenoses, also providing a possible explanation for the prior epidemiological and clinical observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased resting heart rate (rHR), which is easily measurable in clinical practice, has been shown to be an independent risk factor for cardiovascular death in a nondiabetic population [13][14][15][16]. Recently, rHR has also been shown to be valuable in estimating the risk of cardiovascular death in patients with type 2 diabetes [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…Resting heart (pulse) rate (RPR) is a potentially useful measure for neurological fitness because it is: a) a neurologicallybased [1][2][3] and b) supported by outcomes research (which typically shows that a lower RPR is associated with better outcomes compared to a higher RPR). [4][5][6] A variety of health care providers use RPR including nurses, physicians, and chiropractors.…”
Section: Introductionmentioning
confidence: 99%